Effects of Coconut Water-Based Extender on Motility, Viability, Morphology and Membrane Integrity of Refrigerated (4°C) Canine Spermatozoa - Meena, Abhay Kumar; Saraswat, Chandra Shekher; Yadav , Sumit Prakash (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The objective of this study was to determine the effect of a coconut water-based extender on the quality parameters of dog semen (n=24 ejaculates) during refrigeration (4°C) preservation up to 72 h. Four ejaculates per dog were collected from 6 dogs by digital manipulation. All fresh ejaculates were evaluated for macroscopic and microscopic semen evaluation tests. The semen samples were then extended in a coconut water-based extender using a split sample technique. The diluted semen was kept in a refrigerator for preservation at 4°C and evaluated at 0, 24, 48, and 72 h for sperm quality parameters. The sperm motility significantly reduced over a period of time from 0 to 72 h. The live sperm percentage did not differ significantly at 0, 24 and 48 h of preservation. However, there was a significant drop in live sperm percentage at 72 h. The percent sperm abnormalities were significantly increased from 24, 48 to 72 h of preservation. In coconut water-based extender there was a significant difference in intact plasma membrane percentage at different time slots (0, 24, 48 and 72 h). It was concluded that coconut water-based extender can preserve canine sperm for up to 48 h while maintaining sperm motility and viability above 50%. Sperm abnormalities remained within 20% and plasma membrane integrity above 60% both were maintained up to 72 h of semen preservation.